ANALYSIS TYPES OF CONFLICT USED BY THE MAIN CHARACTER IN SPIDERMAN FAR FROM HOME MOVIE - Adi Yudiyana; Komang Dian Puspita Candra; Desak Putu Eka Pratiwi (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This article discusses the types of conflict used by the main character in Spiderman Far From Home movie. The objectives of this study are to identify the types of conflict the types of conflict faced by the main character and to analyze the conflict management strategies used by the main character in Spiderman Far From Home movie. The source of data was taken from a movie entitled Spiderman Far From Home. The data was analyzed by using a descriptive qualitative method. The data was collected through several steps, such as watching the movie repeatedly, then note the points and last, choosing the data that deals with problem. The conflict in this study was analyzed based on the theory proposed by Kenney (1966) and the way conflict management strategies was analyzed based on the theory proposed by Kenney (1966). Based on the results of the analysis, it can be described that the types of conflict faced by the main character found as external conflict, namely man against man. The external conflict that is faced by the main character includes the family environment and the living environment. In resolves the conflict the main character uses conflict management such as competition strategy.